Level of understanding zakat income among iNED staff / Mohamad Hafizuddin Md Ramly - Md Ramly, Mohamad Hafizuddin (Academy of Contemporary Islamic Studies, 2018)
Zakat on incomes is one of the obligations that must be taken by the muslim in the world and should be fulfill based on the islamic fatwa. Most of the Malaysia muslim may not really understanding about the zakat on incomes that need to be issuing. Among of the muslim in Malaysia may already not understanding about zakat on incomes with properly and continues to give a bad impact for the islamic economic. Furthermore, there are more of the muslim were detected by the zakat center which not issuing th zakat on incomes. The research is attempt to identify every part of the objective which mean, its try to identify the understanding level of zakat on income among workers and followed by the next objective is attempt to identify the significant differences level of understanding zakat on incomes. For the last, the researcher is going to produce the profile level of understanding toward zakat on income among Ined staff. The main method that has using by the researcher is questionnaire method that providing 79 questionnaire that has been distributed to the respondent and continues to collapsed a relevant data that is able to accomplished overall of this chapters with properly. The first impression is able to guide every Ined staff to understand and continues to give more awareness to them with properly. This guide will lead them to have awareness for issuing the zakat on incomes with properly that based on the Islamic law that has stipulated by the Islamic fatwa. Lastly, this method will give more benefit whether to the government or private in increasing the islamic economic in future.